On Periodic Solutions for Coupled Systems with Caputo Tempered Fractional Derivative (Letters in Nonlinear Analysis and its Applications, 2024)
The main goal of this paper is to study the existence and uniqueness of periodic solutions for coupled system with Caputo tempered  fractional derivative. The proofs are based upon the coincidence degree theory of Mawhin. An example is constructed to authenticate and affirm the main findings.
Keywords: Coincidence degree theory; existence; uniqueness; Tempered fractional operators; coupled system